Communities of resistance and resilience in the post-industrial city : a transnational perspective from Lyon and Pittsburgh, 1980-2010 - Holland, Daniel (College teacher) (New York, NY : Routledge, 2024)
"This book is about the grassroots community revitalization movement in Pittsburgh, Pennsylvania, and Lyon, France, between 1980 and 2010, an extension of the post-WWII civil rights campaign that is rarely considered. This is of great use to scholars of transatlantic history as well as a general audience interested in modern social movements in the United States and France"--
Keywords: Urban renewal -- Pennsylvania -- Pittsburgh; Urban renewal -- France -- Lyon; Social movements -- Pennsylvania -- Pittsburgh; Social movements -- France -- Lyon; Pittsburgh (Pa.) -- History; Lyon (France) -- History; HISTORY / General; HISTORY / Europe / France; HISTORY / Historical Geography